PENERAPAN MODL PEMBELAJARAN TREFFINGER DALAM UPAYA PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMP - Onah Rohanah; Zuli Nuraeni; Abdul Rasyid (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2017)
Application of Learning Model of Treffinger in Improvement of MathematicalReasoning Ability of Junior High School Students, Mathematics Education StudyProgram (PMTK) STKIP Muhammadiyah Kuningan, 2017. This study aims to examinewhether the improvement of students' mathematical reasoning using Treffingerlearning model is better than improving the ability of mathematical reasoning Studentsusing the direct learning model, examining whether improving students' mathematicalreasoning abilities by using the Treffinger learning model is in the high category, aswell as to examine how students respond to the Treffinger learning model. This type ofresearch is quasi experimental with non-equivalent control group design. The researchvariables consist of one independent variable that is Treffinger learning model and onedependent variable that is students' mathematical reasoning ability. The studypopulation consisted of all students of class VII (Seven) academic year 2016/2017SMP Negeri 4 Kuningan, consisting of class VII-A as experimental class and class VIIC as control class. The study used a description test instrument to evaluate students'mathematical reasoning abilities as well as to use a student response questionnaire tofind out the student's response to the applied learning. To compare the capabilities ofboth classes of researchers using one-way t test for two independent samples. Whileto test the hypothesis about improving the reasoning ability of mathematic researcheruse comparison gain test. The results showed that improving students' mathematicalreasoning ability by using Treffinger learning model is better than direct learningmodel. For the second hypothesis the improvement of the learning model using theTreffinger learning model is not in the high category. For the third hypothesis students'responses show almost entirely positive responses to the Treffinger learning model